Method for preparing aluminum-doped modified lithium iron manganese phosphate positive electrode material from lithium extraction by-product of waste lithium ion battery

By the aluminum mixing of lithium lithium bittites of waste lithium ion batteries, the problem of poor electrochemical properties caused by aluminum impurities in orthopedic materials for recycling and reinstallation of recycling, improving the conductivity and electrochemical performance of the materials, realizing resources, and realizing resources. Cycle use.

CN119381608AActive Publication Date: 2025-01-28HEFEI UNIV OF TECH +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411493513.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-28
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The recycled and remade lithium-ion battery cathode material has deteriorated electrochemical performance due to the presence of metal aluminum impurities, and the solid phase direct recycled material is difficult to meet the needs of commercial applications.

Method used

By mixing aluminum mixing the lithium -lithium -bifling by -products of the waste lithium ion battery, the use of aluminum ions to be doped into the crystal cells of manganese iron phosphate iron phosphate iron phosphate iron phosphate iron phosphate iron phosphate iron phosphate iron phosphate performance.

Benefits of technology

It effectively solves the shortcomings of the existence of metal aluminum impurities, improves the electrochemical properties of materials, is suitable for the application of energy storage batteries, and realizes the recycling of lithium, iron, manganese, phosphorus and aluminum.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381608A_ABST
    Figure CN119381608A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing an aluminum-doped modified lithium iron manganese phosphate positive electrode material from a lithium extraction byproduct of a waste lithium ion battery, which comprises the following steps of: converting metal aluminum in waste lithium iron phosphate positive electrode powder and waste lithium manganate positive electrode powder into aluminum ions; and doping into unit cells of the lithium manganese iron phosphate through ion diffusion in the subsequent calcining process, so as to obtain the aluminum-doped modified lithium manganese iron phosphate positive electrode material. According to the method, the lithium manganese iron phosphate positive electrode material is subjected to aluminum ion doping modification by utilizing trace metal aluminum impurities in the waste electrode material, so that the electrochemical performance of the lithium manganese iron phosphate positive electrode material can be effectively improved, and the problem that the electrochemical performance of a solid-phase direct regeneration material is difficult to meet commercial application requirements is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing an aluminum-doped modified lithium manganese iron phosphate positive electrode material from lithium extraction byproducts of waste lithium ion battery electrode materials, and belongs to the field of lithium ion battery recovery and positive electrode material preparation. Background Art

[0002] Lithium-ion batteries are widely used in new energy vehicle power batteries due to their high energy density and low cost. Due to capacity decay, lithium-ion power batteries will face retirement after 5 to 8 years of use. It is estimated that the retired power lithium batteries will reach 134.49GWh in 2025, and the retired volume will reach 803,600 tons. The recycling and treatment of waste lithium batteries and the remanufacturing of lithium-ion battery electrode materials are important measures to achieve the sustainable development of lithium-ion batteries.

[0003] At present, the mainstream methods of lithium-ion battery recycling include hydrometallurgy and pyrometallurgy. However, hydrometallurgical recycling has complicated steps and produces a large amount of wastewater; pyrometallurgy consumes a lot of energy, it is difficult to remove metal impurities, and emits toxic fumes. In addition, the by-products of lithium extraction from both methods, iron phosphate and manganese dioxide, are directly discarded in most cases, resulting in a waste of resources and environmental risks. The current research difficulties are how to make high-value use of the by-products after lithium extraction and how to deal with impurities in waste positive electrode mixed powder on a green and environmentally friendly basis.

[0004] Most of the existing technologies for recycling waste lithium-ion battery positive electrode materials and preparing new positive electrode materials by solid phase method are based on waste positive electrode materials obtained by manual or automatic fine sorting, and do not involve the treatment of metal impurities. The research of the present invention found that: retired lithium iron phosphate batteries and retired lithium manganese oxide batteries are discharged and disassembled to obtain battery cells, and the residual electrolyte and decomposition binder are removed by 500°C negative pressure pyrolysis treatment under an inert atmosphere, and then the mixed material is crushed, screened, air-selected, magnetically separated, ammonia leached to remove copper and flotation treatment (due to the different densities of waste positive and negative electrode powders, the negative electrode graphite powder will float in the flotation tank, and the positive electrode powder will sink to the bottom, and then a collector and a foaming agent are added to scrape and bubble, and finally filtered and dried), so as to obtain waste positive electrode powder. Subsequently, they are subjected to acid leaching for lithium extraction (acetic acid is used for waste lithium iron phosphate positive electrode powder, and sulfuric acid is used for waste lithium manganese oxide positive electrode powder), and iron phosphate and manganese dioxide powders, which are lithium byproducts, are obtained by filtering and drying. When the recovered lithium extraction byproduct is used as raw material and the electrode material is prepared by adding appropriate lithium source and phosphorus source for application in lithium-ion batteries, the trace amount of metal impurities may cause the crystal structure of the positive electrode material to tend to a metastable state during the battery charging and discharging process, thereby causing the battery performance to decay. Among them, the influence of aluminum impurities is the most obvious. Considering Al 3+ / Al's thermodynamic standard electrode potential (1.38 V vs Li + / Li) is much lower than the normal working potential of most positive electrodes. Therefore, aluminum metal impurities will not only reduce the performance of existing 4V lithium-ion batteries, but also trigger a series of side reactions. In severe cases, the aluminum fragments produced can cause internal short circuits and lead to battery failure. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a method for preparing aluminum-doped modified lithium iron manganese phosphate positive electrode material from lithium extraction byproducts of waste lithium-ion batteries, aiming to solve the problem that the electrochemical performance of the recycled and re-prepared positive electrode material deteriorates due to the presence of metal aluminum impurities. By converting the metal aluminum therein into aluminum ions and doping it into the unit cell of lithium iron manganese phosphate through ion diffusion during the subsequent calcination and re-preparation process, not only the shortcomings of the metal aluminum impurities are solved, but also the conductivity of the material grains is improved; the relevant electrochemical properties of the re-prepared material can be improved by aluminum doping modification, which is suitable for application in energy storage batteries.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solution:

[0007] A method for preparing an aluminum-doped modified lithium iron manganese phosphate positive electrode material from a lithium extraction byproduct of a waste lithium-ion battery, comprising the following steps:

[0008] Step 1: Retired lithium iron phosphate batteries and retired lithium manganese oxide batteries are processed respectively, thereby obtaining waste lithium iron phosphate positive electrode powder and waste lithium manganese oxide positive electrode powder respectively;

[0009] Step 2: treating the waste lithium iron phosphate positive electrode powder with a mixed acid leaching of acetic acid and phosphoric acid to leach lithium ions to produce iron phosphate precipitation, and at the same time converting the aluminum element into aluminum ions; then adjusting the pH of the system with a lithium hydroxide solution to convert the aluminum ions into aluminum phosphate precipitation; the obtained precipitate is washed with ethanol, filtered and dried to obtain a lithium extraction byproduct A;

[0010] Using a mixture of sulfuric acid and phosphoric acid to leaching the waste lithium manganate positive electrode powder, so that lithium ions are leached to produce manganese dioxide precipitation, and aluminum is converted into aluminum ions; then the pH of the system is adjusted with a lithium hydroxide solution to convert aluminum ions into aluminum phosphate precipitation; the obtained precipitate is washed with ethanol, filtered and dried to obtain a lithium extraction byproduct B;

[0011] According to the ratio of iron and manganese in the target product, the lithium extraction by-product A and the lithium extraction by-product B are uniformly mixed to obtain a mixed powder C;

[0012] Step 3: Determine the content of each element in the mixed powder C (which can be determined using an inductively coupled plasma spectrometer), adjust the stoichiometric ratio of lithium, iron, manganese, phosphorus and aluminum in the mixed powder C to within the range of 1-1.05: 0.64-0.68: 0.3: 1: 0.02-0.06 by adding a lithium source, a phosphorus source and an aluminum source, and add 10-20% of glucose or sucrose as a carbon source and a reducing agent based on the mass of the mixed powder C, and mix by solid phase ball milling to obtain a mixed powder D;

[0013] Step 4: Place the mixed powder D in a corundum calcining boat and calcine it under an inert atmosphere to obtain an aluminum-doped modified lithium manganese iron phosphate positive electrode material.

[0014] Furthermore, the specific method of step 1 is: first, the retired lithium iron phosphate battery and the retired lithium manganese oxide battery are discharged and disassembled to obtain battery cells, and the residual electrolyte and the decomposed binder are removed by 500°C negative pressure pyrolysis treatment under an inert atmosphere, and then the two battery cells are crushed, screened, air-selected, magnetically separated, ammonia leached to remove copper, and flotation to remove graphite / carbon, respectively, so as to obtain the corresponding waste lithium iron phosphate positive electrode powder and waste lithium manganese oxide positive electrode powder;

[0015] Furthermore, in step 1, based on the total mass of the waste lithium iron phosphate positive electrode powder or the waste lithium manganese oxide positive electrode powder, the content of lithium iron phosphate or lithium manganese oxide in the positive electrode powder is in the range of 95 to 99.9 wt %, the carbon content is in the range of 0.1 to 2 wt %, and the aluminum content is in the range of 0.5 to 1.3 wt %.

[0016] Furthermore, in step 2: the mixed acid used for mixed acid leaching of waste lithium iron phosphate positive electrode powder is a mixture of acetic acid with a concentration of 0.2 to 1.2 mol / L and phosphoric acid with a concentration of 0.5 to 2 mol / L in a volume ratio of 5 to 10:1; the mixed acid used for mixed acid leaching of waste lithium manganese oxide positive electrode powder is a mixture of sulfuric acid with a concentration of 1 to 5 mol / L and phosphoric acid with a concentration of 0.5 to 2 mol / L in a volume ratio of 5 to 10:1.

[0017] Furthermore, in step 2, when preparing lithium extraction by-product A or lithium extraction by-product B, the concentration of lithium hydroxide used is 2 to 2.5 mol / L, and the pH range of the system is adjusted to 3.0 to 4.0.

[0018] Furthermore, in step 3, the solid phase ball milling has a ball milling speed of 150 to 1500 rpm and a ball milling time of 3 to 10 h.

[0019] Furthermore, in step 3: the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium oxalate, lithium phosphate, lithium acetate and lithium dihydrogen phosphate; the phosphorus source is one or more of ammonium dihydrogen phosphate, iron phosphate, lithium phosphate and lithium dihydrogen phosphate; the aluminum source is one or more of aluminum phosphate, aluminum chloride and aluminum oxide.

[0020] Furthermore, in step 4, the calcination is carried out in two steps: first, the temperature is increased to 300-450°C at a heating rate of 1-6°C / min, and the temperature is kept at this temperature for 2-5 hours; then, the temperature is increased to 600-750°C at a heating rate of 1-6°C / min, and the temperature is kept at this temperature for 8-15 hours; finally, the temperature is naturally cooled to room temperature.

[0021] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0022] The invention discloses a method for preparing an aluminum-doped modified lithium iron manganese phosphate positive electrode material from a lithium extraction byproduct of waste lithium-ion battery electrode materials: firstly, retired lithium iron phosphate batteries and retired lithium manganate batteries are treated respectively to obtain waste lithium iron phosphate positive electrode powder and waste lithium manganate positive electrode powder; then, they are subjected to a mixed acid leaching operation for lithium extraction respectively to obtain iron phosphate and manganese dioxide powder as lithium extraction byproducts, and the contained trace aluminum element is converted into aluminum phosphate; the waste positive electrode powder containing a small amount of carbon and a trace amount of aluminum is used as a raw material, the content of each element is determined, and according to the designed stoichiometric ratio of the lithium iron manganese phosphate target product, Determine the iron-manganese ratio, then add appropriate amounts of lithium source, phosphorus source and aluminum source to adjust the lithium, iron, manganese and phosphorus elements in the mixed powder to meet the stoichiometric ratio design requirements, use solid phase ball milling to grind and mix the waste positive electrode powder evenly; at the same time, use the trace aluminum in the recovered powder as the doped aluminum source, convert the metal aluminum therein into aluminum ions, and dope it into the unit cell of lithium iron manganese phosphate through ion diffusion during the subsequent calcination and re-preparation process, which not only solves the shortcomings of the metal aluminum impurities, but also improves the conductivity of the material grains; the electrochemical properties of the re-prepared material are improved by aluminum doping modification, and it is suitable for application in energy storage batteries. The method of the present invention uses aluminum impurities generated in the pretreatment process of waste batteries as doping raw materials to regenerate waste positive electrode materials into aluminum doped modified positive electrode materials. This method can effectively solve the problem of low material discharge capacity caused by metal aluminum impurities in the recycled and re-prepared positive electrode materials, and the problem that solid phase direct regeneration materials are difficult to meet the needs of commercial applications, thereby realizing the recycling of lithium, iron, manganese, phosphorus and aluminum elements in retired lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the XRD pattern of the undoped lithium manganese iron phosphate positive electrode material obtained in Comparative Example 1;

[0024] Figure 2This is the XRD pattern of the aluminum-doped modified lithium iron phosphate positive electrode material obtained in Example 1;

[0025] Figure 3 This is a FESEM photo of the undoped lithium manganese iron phosphate positive electrode material obtained in Comparative Example 1;

[0026] Figure 4 This is a FESEM photo of the aluminum-doped modified lithium iron phosphate positive electrode material obtained in Example 1;

[0027] Figure 5 This is the EDS spectrum of the aluminum-doped modified lithium iron phosphate positive electrode material obtained in Example 1;

[0028] Figure 6 This is the XPS spectrum of the aluminum-doped modified lithium iron phosphate positive electrode material obtained in Example 1;

[0029] Figure 7 The first cycle charge and discharge curves of button cells prepared with the undoped lithium manganese iron phosphate positive electrode material obtained in Comparative Example 1 and the aluminum-doped modified lithium iron phosphate positive electrode material obtained in Example 1 at a current density of 0.1C;

[0030] Figure 8 This is a rate performance diagram of button cells prepared from the undoped lithium manganese iron phosphate positive electrode material obtained in Comparative Example 1 and the aluminum-doped modified lithium iron phosphate positive electrode material obtained in Example 1.

[0031] Fig. 9 The first cycle charge and discharge curve of the button cell prepared with the aluminum-doped modified lithium iron phosphate positive electrode material obtained in Example 2 at a current density of 0.1C

[0032] Fig.10 The first cycle charge and discharge curve of the button cell prepared with the aluminum-doped modified lithium iron phosphate positive electrode material obtained in Example 3 at a current density of 0.1C DETAILED DESCRIPTION

[0033] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.

[0034] Example 1

[0035] This embodiment provides a method for preparing an aluminum-doped modified lithium manganese iron phosphate positive electrode material from a lithium extraction byproduct of a waste lithium-ion battery, and the specific steps are as follows:

[0036] Step 1: First, the retired lithium iron phosphate batteries and retired lithium manganese oxide batteries are discharged and disassembled to obtain battery cells, and the residual electrolyte and decomposed binder are removed by 500°C negative pressure pyrolysis treatment under a nitrogen atmosphere. The two types of battery cells are then crushed, screened, air-separated, magnetically separated, ammonia leached to remove copper, and flotation to remove graphite / carbon to obtain waste lithium iron phosphate positive electrode powder and waste lithium manganese oxide positive electrode powder.

[0037] Step 2: 1.2 mol / L acetic acid and 1.2 mol / L phosphoric acid are mixed in a volume ratio of 5:1 to obtain a mixed acid A, and the waste lithium iron phosphate positive electrode powder is immersed in the mixed acid A. After soaking at room temperature for 1 hour, the pH is adjusted to 4.0 with a 2 mol / L lithium hydroxide solution. The resulting precipitate (iron phosphate precipitate and aluminum phosphate precipitate) is washed with ethanol, filtered and dried at 100°C to obtain a lithium extraction by-product A.

[0038] 2 mol / L sulfuric acid and 1.2 mol / L phosphoric acid were mixed in a volume ratio of 5:1 to obtain a mixed acid B. The waste lithium manganese oxide positive electrode powder was immersed in the mixed acid B. After soaking at room temperature for 3 hours, the pH was adjusted to 3.0 with a 2 mol / L lithium hydroxide solution. The resulting precipitates (manganese dioxide precipitates and aluminum phosphate precipitates) were washed with ethanol, filtered and dried at 100°C to obtain a lithium extraction by-product B.

[0039] According to the iron-manganese ratio in the target product (iron-manganese molar ratio is 0.68:0.3), the lithium extraction by-product A and the lithium extraction by-product B are ground and mixed evenly to obtain a mixed powder C.

[0040] Step 3: Use an inductively coupled plasma spectrometer to determine the content of each element C in the mixed powder obtained in step 2. According to the designed stoichiometric ratio of the target product of lithium iron manganese phosphate, the stoichiometric ratio of lithium, iron, manganese, phosphorus and aluminum in the mixed powder C is adjusted to 1.05:0.68:0.3:1:0.02 by adding lithium carbonate, lithium dihydrogen phosphate and aluminum phosphate, and 10% of the mass of glucose is added as a carbon source and reducing agent. After mixing by solid phase ball milling (ball milling speed is 1200 rpm, ball milling time is 6 h), mixed powder D is obtained.

[0041] Step 4: Place the mixed powder D in a corundum sintering boat and calcine it under an argon atmosphere (first heat it to 400°C at a heating rate of 4°C / min, keep it warm for 2 hours, then heat it to 600°C at a heating rate of 2°C / min, keep it warm for 8 hours, and finally cool it naturally to room temperature) to obtain an aluminum-doped modified lithium manganese iron phosphate positive electrode material.

[0042] The aluminum-doped modified lithium iron phosphate positive electrode material obtained in step 4 of this embodiment was fully mixed with acetylene black and polyvinylidene fluoride (PVDF) in a ratio of 8:1:1 (mass ratio), and NMP (1-methyl-2-pyrrolidone) was added to make a paste and evenly coated on aluminum foil with a coating thickness of 75 μm. After drying at 80°C, rolling and cutting, a positive electrode sheet with a diameter of 12 mm was made, and vacuum dried for use. A metal lithium sheet was used as the negative electrode and a Cellgard 2400 polypropylene film was used as a diaphragm. An experimental battery was assembled in an argon glove box, and then a constant voltage and constant current charge and discharge test was performed on the battery at 25°C.

[0043] Comparative Example 1

[0044] This comparative example provides a method for preparing an undoped modified lithium iron manganese phosphate positive electrode material from a lithium extraction byproduct of a waste lithium ion battery, and the specific steps are as follows:

[0045] Step 1: First, the retired lithium iron phosphate batteries and retired lithium manganese oxide batteries are discharged and disassembled to obtain battery cells, and the residual electrolyte and decomposed binder are removed by 500°C negative pressure pyrolysis treatment under a nitrogen atmosphere. The two types of battery cells are then crushed, screened, air-separated, magnetically separated, ammonia leached to remove copper, and flotation to remove graphite / carbon to obtain waste lithium iron phosphate positive electrode powder and waste lithium manganese oxide positive electrode powder.

[0046] Step 2: Immerse the waste lithium iron phosphate positive electrode powder in 1.2 mol / L acetic acid. After soaking at room temperature for 1 hour, the resulting precipitate (iron phosphate precipitate) is washed with ethanol, filtered and dried at 100°C to obtain lithium extraction by-product A.

[0047] The waste lithium manganese oxide positive electrode powder was immersed in 2 mol / L sulfuric acid at room temperature for 3 hours. The resulting precipitate (manganese dioxide precipitate) was washed with ethanol, filtered and dried at 100°C to obtain a lithium extraction by-product B.

[0048] According to the iron-manganese ratio in the target product (iron-manganese molar ratio is 0.7:0.3), the lithium extraction by-product A and the lithium extraction by-product B are ground and mixed evenly to obtain a mixed powder C.

[0049] Step 3: Use an inductively coupled plasma spectrometer to determine the content of each element C in the mixed powder obtained in step 2. According to the designed stoichiometric ratio of the target product of lithium iron manganese phosphate, the stoichiometric ratio of lithium, iron, manganese and phosphorus in the mixed powder C is adjusted to 1:0.7:0.3:1 by adding lithium carbonate and lithium dihydrogen phosphate, and 10% of the mass of the mixed powder C is glucose as a carbon source and reducing agent. After mixing by solid phase ball milling (ball milling speed is 1200 rpm, ball milling time is 6h), mixed powder D is obtained.

[0050] Step 4: Place the mixed powder D in a corundum sintering boat and calcine it under an argon atmosphere (first heat it to 400°C at a heating rate of 4°C / min, keep it warm for 2 hours, then heat it to 600°C at a heating rate of 2°C / min, keep it warm for 8 hours, and finally cool it naturally to room temperature) to obtain an undoped modified lithium manganese iron phosphate positive electrode material.

[0051] The undoped modified lithium iron phosphate positive electrode material obtained in step 4 of this comparative example was fully mixed with acetylene black and polyvinylidene fluoride (PVDF) in a ratio of 8:1:1 (mass ratio), and NMP (1-methyl-2-pyrrolidone) was added to make a paste and evenly coated on aluminum foil with a coating thickness of 75 μm. After drying at 80°C, rolling and cutting, a positive electrode sheet with a diameter of 12 mm was made, and vacuum dried for use. A metal lithium sheet was used as the negative electrode and a Cellgard 2400 polypropylene film was used as a diaphragm. An experimental battery was assembled in an argon glove box, and then a constant voltage and constant current charge and discharge test was performed on the battery at 25°C.

[0052] Figure 1 This is the XRD diagram of the undoped lithium manganese iron phosphate positive electrode material obtained in Comparative Example 1. Figure 2 The XRD diagram of the aluminum-doped modified lithium iron phosphate cathode material obtained in Example 1. It can be seen from the figure that both materials can be indexed as orthorhombic olivine structure with space group Pnma. 2+ Occupies the 4a position of the octahedron, Li + Occupies the 4c ​​position of the octahedron. Both the edge-sharing LiO4 and corner-sharing FeO6 octahedra are parallel to the c-axis and aligned along the b-axis.

[0053] Table 1 shows the unit cell parameters of aluminum-doped modified lithium manganese iron phosphate and undoped lithium manganese iron phosphate

[0054]

[0055] Table 1 shows that the unit cell parameters a, b, c and unit cell volume of the co-doped samples are reduced, which is due to the Al 3+ Doping may mainly occur in Li + Substitution, Al 3+ The radius (0.050nm) is smaller than Fe 2+ The radius (0.064nm) of the lattice parameter leads to a decrease in the unit cell parameter. At the same time, the bond energy of Al-O is greater than that of Fe-O, which reduces the unit cell volume. The decrease in the lattice parameter b can shorten the Li + The diffusion distance is shortened, thereby improving the electronic conductivity and lithium ion diffusion rate of the lithium iron phosphate electrode material.

[0056] Figure 3 and Figure 4The FESEM photos of the undoped lithium iron manganese phosphate positive electrode material obtained in Comparative Example 1 and the aluminum-doped modified lithium iron phosphate positive electrode material obtained in Example 1 are shown respectively. It can be seen from the figure that the particle size of the undoped lithium iron manganese phosphate is between 0.5 μm and 2 μm, while the particle size of the aluminum-doped modified lithium iron manganese phosphate positive electrode material is reduced and more uniform (particle size is between 0.1 μm and 1 μm). The reduction in particle size helps to reduce the lithium ion diffusion path and increase the high-rate discharge performance of lithium iron phosphate.

[0057] Figure 5 This is the EDS spectrum of the aluminum-doped modified lithium iron phosphate positive electrode material obtained in Example 1. From the figure, it can be seen that the stoichiometric ratio of Fe:Mn:P:Al≈0.68:0.3:1:1:0.02 is basically in line with the design value within the error range.

[0058] Figure 6 This is the XPS spectrum of the aluminum-doped modified lithium iron phosphate positive electrode material obtained in Example 1. It can be seen from the figure that the 2p 3 / 2 The spin splitting orbit and the satellite peak characteristics unique to trivalent aluminum were observed, proving that aluminum was doped into the crystal cell of the lithium iron phosphate material in the form of trivalent ions.

[0059] Figure 7 The first cycle charge and discharge curves of button cells prepared from the undoped lithium manganese iron phosphate positive electrode material obtained in Comparative Example 1 and the aluminum-doped modified lithium manganese iron phosphate positive electrode material obtained in Example 1 at a current density of 0.1C. It can be seen from the figure that the discharge specific capacity of the aluminum-doped modified lithium manganese iron phosphate is 162.85 mAh / g, and the discharge specific capacity of the undoped modified lithium manganese iron phosphate is 155.71 mAh / g.

[0060] Figure 8 The figure is a rate performance diagram of button cells prepared from the undoped lithium iron manganese phosphate positive electrode material obtained in Comparative Example 1 and the aluminum-doped modified lithium iron phosphate positive electrode material obtained in Example 1. It can be seen from the figure that the degree of electrode polarization of the aluminum-doped modified lithium iron manganese phosphate positive electrode material during high-rate charge and discharge is significantly lower than that of the waste positive electrode powder, and the discharge specific capacity is significantly higher than that of the undoped modified lithium iron manganese phosphate positive electrode material.

[0061] Example 2

[0062] This embodiment provides a method for preparing an aluminum-doped modified lithium manganese iron phosphate positive electrode material from a lithium extraction byproduct of a waste lithium-ion battery, and the specific steps are as follows:

[0063] Step 1: First, the retired lithium iron phosphate batteries and retired lithium manganese oxide batteries are discharged and disassembled to obtain battery cells, and the residual electrolyte and decomposed binder are removed by 500°C negative pressure pyrolysis treatment under a nitrogen atmosphere. The two types of battery cells are then crushed, screened, air-sorted, magnetically separated, ammonia leached to remove copper, and flotation to remove graphite / carbon to obtain waste lithium iron phosphate positive electrode powder and waste lithium manganese oxide positive electrode powder.

[0064] Step 2: 0.8 mol / L acetic acid and 1.2 mol / L phosphoric acid are mixed in a volume ratio of 5:1 to obtain a mixed acid A, and the waste lithium iron phosphate positive electrode powder is immersed in the mixed acid A. After soaking at room temperature for 1 hour, the pH is adjusted to 4.0 with a 2 mol / L lithium hydroxide solution. The resulting precipitate (iron phosphate precipitate and aluminum phosphate precipitate) is washed with ethanol, filtered and dried at 100°C to obtain a lithium extraction by-product A.

[0065] 3 mol / L sulfuric acid and 1.2 mol / L phosphoric acid were mixed in a volume ratio of 5:1 to obtain a mixed acid B. The waste lithium manganese oxide positive electrode powder was immersed in the mixed acid B. After soaking at room temperature for 3 hours, the pH was adjusted to 3.0 with a 2 mol / L lithium hydroxide solution. The resulting precipitates (manganese dioxide precipitates and aluminum phosphate precipitates) were washed with ethanol, filtered and dried at 100°C to obtain a lithium extraction by-product B.

[0066] According to the iron-manganese ratio in the target product (iron-manganese molar ratio is 0.66:0.3), the lithium extraction by-product A and the lithium extraction by-product B are ground and mixed evenly to obtain a mixed powder C.

[0067] Step 3: Use an inductively coupled plasma spectrometer to determine the content of each element in the mixed powder C obtained in step 2. According to the designed stoichiometric ratio of the target product of lithium iron manganese phosphate, the stoichiometric ratio of lithium, iron, manganese, phosphorus and aluminum in the mixed powder C is adjusted to 1:0.66:0.3:1:0.04 by adding lithium carbonate, lithium dihydrogen phosphate and aluminum phosphate, and 10% of the mass of glucose is added as a carbon source and reducing agent. After mixing by solid phase ball milling (ball milling speed is 1200 rpm, ball milling time is 6 h), mixed powder D is obtained.

[0068] Step 4: Place the mixed powder D in a corundum sintering boat and calcine it under an argon atmosphere (first heat it to 400°C at a heating rate of 4°C / min, keep it warm for 2 hours, then heat it to 600°C at a heating rate of 2°C / min, keep it warm for 8 hours, and finally cool it naturally to room temperature) to obtain an aluminum-doped modified lithium manganese iron phosphate positive electrode material.

[0069] Fig. 9This is the first cycle charge and discharge curve of a button cell prepared from the aluminum-doped modified lithium iron phosphate positive electrode material obtained in Example 2 at a current density of 0.1C. It can be seen from the figure that the discharge specific capacity of the material is 157.25 mAh / g.

[0070] Example 3

[0071] This embodiment provides a method for preparing an aluminum-doped modified lithium manganese iron phosphate positive electrode material from a lithium extraction byproduct of a waste lithium-ion battery, and the specific steps are as follows:

[0072] Step 1: First, the retired lithium iron phosphate batteries and retired lithium manganese oxide batteries are discharged and disassembled to obtain battery cells, and the residual electrolyte and decomposed binder are removed by 500°C negative pressure pyrolysis treatment under a nitrogen atmosphere. The two types of battery cells are then crushed, screened, air-sorted, magnetically separated, ammonia leached to remove copper, and flotation to remove graphite / carbon to obtain waste lithium iron phosphate positive electrode powder and waste lithium manganese oxide positive electrode powder.

[0073] Step 2: 1 mol / L acetic acid and 1.2 mol / L phosphoric acid are mixed in a volume ratio of 5:1 to obtain a mixed acid A, and the waste lithium iron phosphate positive electrode powder is immersed in the mixed acid A. After soaking at room temperature for 1 hour, the pH is adjusted to 4.0 with a 2 mol / L lithium hydroxide solution. The resulting precipitate (iron phosphate precipitate and aluminum phosphate precipitate) is washed with ethanol, filtered and dried at 100°C to obtain a lithium extraction by-product A.

[0074] 1 mol / L sulfuric acid and 1.2 mol / L phosphoric acid were mixed in a volume ratio of 5:1 to obtain a mixed acid B. The waste lithium manganese oxide positive electrode powder was immersed in the mixed acid B. After soaking at room temperature for 3 hours, the pH was adjusted to 3.0 with a 2 mol / L lithium hydroxide solution. The resulting precipitates (manganese dioxide precipitates and aluminum phosphate precipitates) were washed with ethanol, filtered and dried at 100°C to obtain a lithium extraction by-product B.

[0075] According to the iron-manganese ratio in the target product (iron-manganese molar ratio is 0.64:0.3), the lithium extraction by-product A and the lithium extraction by-product B are ground and mixed evenly to obtain a mixed powder C.

[0076] Step 3: Use an inductively coupled plasma spectrometer to determine the content of each element in the mixed powder C obtained in step 2. According to the designed stoichiometric ratio of the target product of lithium iron manganese phosphate, the stoichiometric ratio of lithium, iron, manganese, phosphorus and aluminum in the mixed powder C is adjusted to 1:0.64:0.3:1:0.06 by adding lithium carbonate, lithium dihydrogen phosphate and aluminum phosphate, and 10% of the mass of glucose is added as a carbon source and reducing agent. After mixing by solid phase ball milling (ball milling speed is 1200 rpm, ball milling time is 6h), mixed powder D is obtained.

[0077] Step 4: Place the mixed powder D in a corundum calcining boat and calcine it under an inert atmosphere such as nitrogen or argon (first heat it to 350°C at a heating rate of 4°C / min, keep it warm for 2 hours, then heat it to 700°C at a heating rate of 2°C / min, keep it warm for 8 hours, and finally cool it naturally to room temperature) to obtain an aluminum-doped modified lithium manganese iron phosphate positive electrode material.

[0078] Fig.10 This is the first cycle charge and discharge curve of a button cell prepared with the doped and modified lithium iron phosphate positive electrode material obtained in Example 3 at a current density of 0.1C. It can be seen from the figure that the discharge specific capacity of the material is 150.73 mAh / g.

[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. All modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing aluminum-doped modified lithium iron manganese phosphate positive electrode material from lithium extraction byproducts of waste lithium-ion batteries, characterized in that: The steps include: Step 1: Retired lithium iron phosphate batteries and retired lithium manganese oxide batteries are processed respectively, thereby obtaining waste lithium iron phosphate positive electrode powder and waste lithium manganese oxide positive electrode powder respectively; Step 2: treating the waste lithium iron phosphate positive electrode powder with a mixed acid leaching of acetic acid and phosphoric acid to leach lithium ions to produce iron phosphate precipitation, and at the same time converting the aluminum element into aluminum ions; then adjusting the pH of the system with a lithium hydroxide solution to convert the aluminum ions into aluminum phosphate precipitation; the obtained precipitate is washed with ethanol, filtered and dried to obtain a lithium extraction byproduct A; Using a mixture of sulfuric acid and phosphoric acid to leaching the waste lithium manganate positive electrode powder, so that lithium ions are leached to produce manganese dioxide precipitation, and aluminum is converted into aluminum ions; then the pH of the system is adjusted with a lithium hydroxide solution to convert aluminum ions into aluminum phosphate precipitation; The obtained precipitate is washed with ethanol, filtered and dried to obtain a lithium extraction byproduct B; According to the ratio of iron and manganese in the target product, the lithium extraction by-product A and the lithium extraction by-product B are uniformly mixed to obtain a mixed powder C; Step 3: Determine the content of each element in the mixed powder C, adjust the stoichiometric ratio of lithium, iron, manganese, phosphorus and aluminum in the mixed powder C within the range of 1-1.05: 0.64-0.68: 0.3: 1: 0.02-0.06 by adding a lithium source, a phosphorus source and an aluminum source, add 10-20% of the mass of the mixed powder C with glucose or sucrose as a carbon source and a reducing agent, and mix by solid phase ball milling to obtain a mixed powder D; Step 4: Place the mixed powder D in a corundum calcining boat and calcine it under an inert atmosphere to obtain an aluminum-doped modified lithium manganese iron phosphate positive electrode material.

2. The method according to claim 1, characterized in that The specific method of step 1 is: first, the retired lithium iron phosphate batteries and retired lithium manganese oxide batteries are discharged and disassembled to obtain battery cells, and the residual electrolyte and decomposed binder are removed by negative pressure pyrolysis treatment under an inert atmosphere. Then, the two types of battery cells are crushed, screened, air-separated, magnetically separated, ammonia leached to remove copper, and flotation to remove graphite / carbon, respectively, so as to obtain the corresponding waste lithium iron phosphate positive electrode powder and waste lithium manganese oxide positive electrode powder, respectively.

3. The method according to claim 1, characterized in that: In step 1, based on the total mass of the waste lithium iron phosphate positive electrode powder or the waste lithium manganese oxide positive electrode powder, the content of lithium iron phosphate or lithium manganese oxide in the positive electrode powder is in the range of 95 to 99.9 wt %, the carbon content is in the range of 0.1 to 2 wt %, and the aluminum content is in the range of 0.5 to 1.3 wt %.

4. The method according to claim 1, characterized in that In step 2: the mixed acid used for mixed acid leaching of waste lithium iron phosphate positive electrode powder is a mixture of acetic acid with a concentration of 0.2 to 1.2 mol / L and phosphoric acid with a concentration of 0.5 to 2 mol / L in a volume ratio of 5 to 10:1; the mixed acid used for mixed acid leaching of waste lithium manganese oxide positive electrode powder is a mixture of sulfuric acid with a concentration of 1 to 5 mol / L and phosphoric acid with a concentration of 0.5 to 2 mol / L in a volume ratio of 5 to 10:

1.

5. The method according to claim 1, characterized in that In step 2, when preparing lithium extraction by-product A or lithium extraction by-product B, the concentration of lithium hydroxide used is 2-2.5 mol / L, and the pH range of the system is adjusted to 3.0-4.

0.

6. The method according to claim 1, characterized in that In step 3, the solid phase ball milling has a ball milling speed of 150 to 1500 rpm and a ball milling time of 6 to 10 h.

7. The method according to claim 1, characterized in that: In step 3, the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium oxalate, lithium phosphate, lithium acetate and lithium dihydrogen phosphate, and the phosphorus source is one or more of ammonium dihydrogen phosphate, iron phosphate, lithium phosphate and lithium dihydrogen phosphate.

8. The method according to claim 1, characterized in that: In step 3, the aluminum source is one or more of aluminum phosphate, aluminum chloride and aluminum oxide.

9. The method according to claim 1, characterized in that: In step 4, the calcination is carried out in two steps: first, the temperature is increased to 300-450°C at a heating rate of 1-6°C / min, and the temperature is kept for 2-5 hours; then, the temperature is increased to 600-700°C at a heating rate of 1-6°C / min, and the temperature is kept for 8-15 hours; finally, the temperature is naturally cooled to room temperature.

10. An aluminum-doped modified lithium manganese iron phosphate positive electrode material prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method of recycling waste lithium iron phosphate battery and lithium manganate battery

    CN106997975A

  • Method for preparing ternary anode material precursor from waste lithium battery anode pieces

    CN108899604A

  • Method for preparing copper-aluminum co-doped modified lithium iron phosphate positive electrode material from waste lithium iron phosphate batteries

    CN115347265A

  • Resource utilization method of waste lithium iron phosphate battery

    CN117712544A

  • Recycling method for nickel-cobalt-manganese positive electrode material and waste nickel-cobalt-manganese positive electrode material

    WO2022237102A1